2019
DOI: 10.1371/journal.pone.0221929
|View full text |Cite
|
Sign up to set email alerts
|

Association of food security and other socio-economic factors with dietary diversity and nutritional statuses of children aged 6-59 months in rural Bangladesh

Abstract: Introduction Dietary diversity score (DDS) is a proxy indicator for measuring nutrient adequacy. In this study, we aimed to identify the nutritional statuses and current patterns of DDS among children between 6–59 months old and their associations with different individual and household level factors in rural Bangladesh. Methods The Nobokoli programme of World Vision Bangladesh was implemented in Mymensingh, Sherpur, Rangpur, Dinajpur, Thakurgaon, Panchagar, and Nilpham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
72
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 61 publications
16
72
2
4
Order By: Relevance
“…Mothers with primary and above school qualification seemed to perform better with respect to IFPs than illiterate mothers. This finding is in agreement with previous studies in Ethiopia and elsewhere [13,42,44,45,75]. This may be explained by educated mothers having better understanding of IYCF itself and/or had exposure to IYCF awareness raising campaigns (through their ability to read leaflets, posters and banners) that have been conducted for several years by the Ministry of Health and development partners in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mothers with primary and above school qualification seemed to perform better with respect to IFPs than illiterate mothers. This finding is in agreement with previous studies in Ethiopia and elsewhere [13,42,44,45,75]. This may be explained by educated mothers having better understanding of IYCF itself and/or had exposure to IYCF awareness raising campaigns (through their ability to read leaflets, posters and banners) that have been conducted for several years by the Ministry of Health and development partners in Ethiopia.…”
Section: Discussionsupporting
confidence: 92%
“…Systematic reviews in 2019 and 2015concluded that depressed women breastfed their child for shorter duration than nondepressed women [23,41]. Other previous studies also reported a negative association between maternal depression and early initiation of breastfeeding [42], complementary feeding initiation [43] and infants' dietary diversity [44,45].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover a cash income >5000 INR was associated with higher Hb increases over time, suggesting that a higher cash flow improves the nutritional outcomes for children early in life. This is in line with published evidence that household wealth status is associated with dietary diversity and nutritional status of Bangladeshi children [126], as well as with hemoglobin concentration of Bangladeshi women due to increased iron intake from animal sources [127]. Therewith, the observed weight gain in our study is rather low, however is in line with other trials not achieving the proposed daily weight gain of 5g/kg/bw.…”
Section: Predictors For the Response Size Of Hemoglobin Increasessupporting
confidence: 93%
“…Systematic reviews in 2019 and 2015concluded that depressed women breastfed their children for shorter duration than non-depressed women [30,31]. Other previous studies also reported a negative association of maternal depression with early initiation of breastfeeding [28], timey complementary feeding initiation [27] and infants' dietary diversity [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…Among the psychosocial factors, prenatal and postnatal depression consistently predicted components of IFPs such as breastfeeding initiation [28,29], exclusive breastfeeding [30][31][32], breastfeeding duration [33] complementary feeding timely initiation [27] and dietary diversity [34,35]. Moreover, researchers reported that other psychosocial factors such as intimate partner violence and maternal social support are important predictors of IFPs.…”
mentioning
confidence: 99%